Digital Marketing Communication in the Electric Vehicle Industry on Social Media: A Content Analysis and Consumer Perception Study of Byd Atto 1 on Instagram and Tiktok - Tiky Perdana, Ahmad; Ardyast Leksono, Rafii (Jurnal Indonesia Sosial Sains, 2026)
The increasing role of social media in digital marketing communication has reshaped how companies engage with consumers, particularly in the electric vehicle (EV) industry. This study aims to analyze the digital marketing communication strategies implemented by BYD for its BYD Atto 1 model on Instagram and TikTok, and to understand how consumer perceptions are shaped through social media interactions. A qualitative case study approach was employed, involving content analysis of BYD Indonesia’s official social media posts and thematic analysis of 150 user comments collected from July to August 2025. The findings reveal that BYD utilizes three primary content types: promotional (e.g., pricing and warranty information), educational (e.g., cost and maintenance comparisons), and branding (e.g., lifestyle and identity messaging). Consumer responses are predominantly positive, with appreciation for the vehicle’s affordable price, modern design, and advanced technology. Some users also expressed purchase intentions. However, concerns regarding battery durability and the availability of charging infrastructure persist. The study concludes that while social media marketing effectively attracts attention and shapes favorable perceptions, addressing consumer concerns through clearer, more comprehensive educational content is essential to build trust and support EV adoption in the context of the energy transition.